1928
DOI: 10.1037/h0070653
|View full text |Cite
|
Sign up to set email alerts
|

Personality and character tests.

Abstract: In addition to the usual summary of articles dealing with personality and character tests, we shall include here titles on ratings, general discussions and experiments bearing directly on this subject. The rapidly developing interest in the physiological and morphological aspects of personality in Europe has resulted in a sufficient number of articles and books to justify a special heading for them. Articles reporting the use of old techniques, because of interest in the results only, are listed in Section G.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1930
1930
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 261 publications
0
2
0
Order By: Relevance
“…This work went by various names-temperament and character also were used. By 1930, May and Hartshorne (1926;May, Hartshorne, & Welty, 1927, 1928, 1930, as cited in Viteles, 1932 had produced five reviews in the Psychological Bulletin in which they showed, for example, what is now called "reliability" or "conscientiousness" was a holistic personality construct they called "consistency." Consistent or integrated individuals, they proposed based on evidence, were predictable in their behavior while inconsistent individuals were not.…”
Section: In the Beginning-the 1920s And 1930smentioning
confidence: 99%
“…This work went by various names-temperament and character also were used. By 1930, May and Hartshorne (1926;May, Hartshorne, & Welty, 1927, 1928, 1930, as cited in Viteles, 1932 had produced five reviews in the Psychological Bulletin in which they showed, for example, what is now called "reliability" or "conscientiousness" was a holistic personality construct they called "consistency." Consistent or integrated individuals, they proposed based on evidence, were predictable in their behavior while inconsistent individuals were not.…”
Section: In the Beginning-the 1920s And 1930smentioning
confidence: 99%
“…Since the early days of applied psychology, researchers have been interested in personality and vocational interests, as well as the association between these two domains (cf. May, Hartshorne, & Welty, 1927, 1928, 1929, 1930). Yet, as has often been the case in psychological research, the lack of comprehensive taxonomies long stalled systematic reviews of their interrelation.…”
Section: Introductionmentioning
confidence: 99%